Structural Basis for a Lethal Mutation in U6 RNA(,) - Sashital, Dipali G. (2003)
U6 RNA is essential for nuclear pre-mRNA splicing and has been implicated directly in catalysis of intron removal. The U80G mutation at the essential magnesium binding site of the U6 3′ intramolecular stem–loop region (ISL) is lethal in yeast. To further understand the structure and function of the U6 ISL, we have investigated the structural basis for the lethal U80G mutation by NMR and optical spectroscopy. The NMR structure reveals that the U80G mutation causes a structural rearrangement within the ISL resulting in the formation of a new Watson–Crick base pair (C67·G80), and disrupts a protonated C67·A79 wobble pair that forms in the wild-type structure. Despite the structural change, the accessibility of the metal binding site is unperturbed, and cadmium titration produces similar phosphorus chemical shift changes for both the U80G mutant and wild-type RNAs. The thermodynamic stability of the U80G mutant is significantly increased (ΔΔG(fold) = −3.6 ± 1.9 kcal/mol), consistent with formation of the Watson–Crick pair. Our structural and thermodynamic data, in combination with previous genetic data, suggest that the lethal basis for the U80G mutation is stem–loop hyperstabilization. This hyperstabilization may prevent the U6 ISL melting and rearrangement necessary for association with U4.